Multiple resistance to toxic metals of the Antarctic cliff microorganisms (island Galindez) - Tashyrev, A. B.; Romanovskaya, V. A.; Rokitko, P. V.; Tashyreva, A. A. (Ukrainian Antarctic Journal, 2012)
The focus of the study is multiple resistance to five toxic metals of 10 microbial strains isolated from the cliffs of Antarctic island Galindez (Vernadsky station). The growth of strains in presence metals which posses replacing (Ni2+, Co2+), oxidative properties (CrO42–) and metals of the "combined" action (Hg2+, Cu2+), both replacing and oxidizing agents, had been studied. The microorganisms were isolated on agar medium containing no metal, and then were grown in liquid medium containing one of these metals. Increasing the concentration of metals in the media naturally decreased the number of viable strains. Thus, all 10 strains were resistant to 0.1 g/l Cu2+, 0.4 g/l - 3 strains, 1.0 g/l - 2 strains, and at 1.25 g/l - only one strain. The highest sensibility strains showed to Hg2+ - which is high potential metal ion (Ео’= + 920 mV), replacing metals in cell enzymes. At a concentration 0.01 g/l Hg2+ grew 6 of 10 strains, and at 0.05 g/l - only 1 strain. The most resistant microorganisms were in relation to Cr(VI). At chromium concentration in cultivation media 1.25 g/l, 2.0 and 20.0 g/l grew, respectively, 8, 3 and 1 strains. The following range of resistance of strains towards specified toxic metal ions is obtained (in g/l): 20.0 Cr(VI) > 2.0 Ni2+ > 1.25 Cu2+ > 0.1 Cо2+ > 0.05 Hg2+. Strain 190n2 showed maximal resistance to metals, it grew at high concentrations of all five metals. Thus, we have shown that Antarctic cliff microorganisms are polyresistant to five the most toxic metals that combine the damaging effects of replacing and oxidizing metals, and metals of combined action.